What makes a space invader? Passenger perceptions of personal space invasion in aircraft travel. Issue 11 (2nd November 2017) - Lewis, Laura; Patel, Harshada; D'Cruz, Mirabelle; Cobb, Sue
Abstract: The invasion of personal space is often a contributory factor to the experience of discomfort in aircraft passengers. This paper presents a questionnaire study which investigated how air travellers are affected by invasions of personal space and how they attempt to adapt to, or counter, these invasions. In support of recent findings on the factors influencing air passenger comfort, the results of this study indicate that the invasion of personal space is not only caused by physical factors (e.g. physical contact with humans or objects), but also other sensory factors such as noise, smells or unwanted eye contact. The findings of this study have implications for the design of shared spaces. Practitioner Summary : This paper presents a questionnaire study which investigated personal space in an aircraft environment. The results highlight the factors which affect the perception of personal space invasion in aircraft and can therefore inform the design of aircraft cabin environments to enhance the passenger experience.